2021
DOI: 10.31763/ijrcs.v1i3.457
|View full text |Cite
|
Sign up to set email alerts
|

Stirring System Design for Automatic Coffee Maker Using OMRON PLC and PID Control

Abstract: The implementation of the use of PLC in this study was designed for a small scale in the process of stirring coffee drinks at a speed of 600 RPM. To get a stable speed so that the water does not overflow, a control system is needed. To get optimal results, a system design that can control the stirring speed is arranged automatically using a Programmable Logic Controller (PLC). This system is designed using a rotary encoder sensor C38S6G5-600B-G24N as a speed reader obtained from the movement of the motor, DC M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The PID control system is a type of feedback control system that utilizes a controller called Proportional-Integral-Derivative (PID) [82], [83], [84], [85], [86], [87], [88], [89]. This type of control system is commonly used in the basic design of motor control systems [90], [91], [92], [93], [94], [95].…”
Section: Pid Controller Designmentioning
confidence: 99%
“…The PID control system is a type of feedback control system that utilizes a controller called Proportional-Integral-Derivative (PID) [82], [83], [84], [85], [86], [87], [88], [89]. This type of control system is commonly used in the basic design of motor control systems [90], [91], [92], [93], [94], [95].…”
Section: Pid Controller Designmentioning
confidence: 99%
“…1 and Fig. 2, two diagrams can be shown that represent each of the DC servo motor circuits, first, and the other represents a block for this motor [41][42][43][44][45]. From Fig.…”
Section: System Description and Mathematical Model Of DC Servomotormentioning
confidence: 99%
“…Although traditional Proportional-Integral-Derivative (PID) control technology can achieve certain results in certain situations, it is hard to cater for the wants of contemporary industrial manufacturing for high precision and stability due to its difficult parameter adjustment and susceptibility to external interference (Tian et al, 2020). For example, Wang team and Setiawan team both proposed controllers based on PID control technology, but the PID controllers proposed all have the problem of unstable control effect (Wang and Lu, 2022;Setiawan and Ma'arif, 2021). Therefore, seeking a new control method to improve the effect of 8BSM is of great significance.…”
Section: Introductionmentioning
confidence: 99%